Arctic explorations : the second Grinnell expedition in search of Sir John Franklin, 1853, '54, '55. - Kane, Elisha Kent, 1820-1857. (Philadelphia: Childs & Peterson; [etc. etc.], 1858)
Added t.-p., engraved, dated 1856. Mode of access: Internet.